Overview of Non-Pharmacological Treatment Option for Adolescent Girls with Dysmenorrhea in Cimahi, West Java, Indonesia - Rahmani, Shofiatunisa Firdhausy; Anwar, Ruswana; Sasongko, Elsa Pudji Setiawati; Ritonga, Mulyanusa Amarullah; Arya, Insi Farisa Desy (Althea Medical Journal, 2024)
Background: Dysmenorrhea is a condition of pain during menstruation that may affect daily activities. The phenomenon of dysmenorrhea in West Java has reached 54,9%. When dysmenorrhea is not treated, it can decrease productivity at school. This study aimed to find out which therapy was more widely used, the reasons for using the therapy, and to identify changes in non-pharmacological therapy as seen from the visual analog scale (VAS) assessment.Methods: This research used quantitative data with a descriptive study conducted with a cross-sectional method, and the instrument used was a questionnaire. The study was conducted in July 2022 with a total sample of 457 participants, and 366 samples met the inclusion criteria. This data analysis used Statistical Package for Social Scientists (SPSS version 28) to identify changes before and after non-pharmacological therapy options and the frequency distribution of the data.Results: The non-pharmacological therapy option was preferred by students (n= 366), and the reasons students used this therapy were seen from various aspects. Rest was the most frequently chosen activity by students (n= 329). All students felt a change in the pain scale before and after using non-pharmacological therapy with the visual analog scale (VAS).Conclusion: Students in grades 1 and 2 of SMAN 1 Cimahi prefer non-pharmacological therapy with rest. They have various aspects of reasoning and feeling changed after using the therapy. There is a change in the pain scale after using non-pharmacological therapy.